Comparison of Transcutaneous and Total Serum Bilirubin Measurements at Five Different Sites in Newborns before and after Phototherapy - Eken, Seda; Ilhan, Ozkan; Hakan, Nilay (Klinische Pädiatrie, 2023)
Objective This study aims to examine the accuracy of transcutaneous bilirubin (TcB) in estimating the total serum bilirubin (TSB) level at five different sites before and immediately after phototherapy.Methods This study prospectively enrolled infants with a gestational age of 34 to 416/7 weeks who were clinically diagnosed with neonatal jaundice and required phototherapy within 28 days after birth. TcB levels were measured on the uncovered four areas (forehead, mid-sternum, abdomen, and interscapular site) and covered hipbone by using the Dräger JM-103 Jaundice Meter before phototherapy and at 0 min after discontinuing phototherapy. Correlation and agreement between TcB and TSB levels were assessed before and after phototherapy.Results We included 108 infants with a mean gestational age of 37.6±1.5 weeks and birth weight of 3108±548 g. A strong significant correlation was found between TSB and TcB measurements at all five sites before phototherapy with the strongest correlation at the interscapular site (r=0.768, p=0.001). The correlation was weakened between TSB and TcB at all five sites after phototherapy; however, the strongest correlation was at the covered hipbone (r=0.619, p=0.001). TcB measurements at all five sites tended to underestimate TSB levels before and after phototherapy. The difference (TcB − TSB) tended to increase with increasing TSB levels.Conclusions TcB levels were most accurately measured at the interscapular site and covered hipbone before and immediately after phototherapy, respectively.
Keywords: transcutaneous; bilirubin; jaundice; hyperbilirubinemia; newborn; phototherapy